Quantum Chemistry Kinetic Analysis for Cracking Reactions of Normal and Iso Hexane Based on Transition State Energetic Evaluation for Production of n-C4 and i-C4 in FCC Process; Mechanisms of Catalytic Reactions (MCR-XII) - Foroutan G. S. Ghazvini Saba (2024, 2024)
Title screen.